The Influence of Capital, Training, and Mentoring on The Success of MSMEs Businesses in The Fashion Sector During The COVID-19 Pandemic in Pekanbaru - Husnul Fikri Al Hakim; Kurniawaty Fitri; Machasin Machasin (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study aims to determine the effect of Capital on the Success of Fashion Sector MSMEs during the Covid-19 Pandemic in Pekanbaru, to determine the effect of Training on the Success of Fashion Sector MSMEs during the Covid-19 Pandemic in Pekanbaru, to determine the effect of Assistance on the Success of Fashion Sector MSMEs during the Covid-19 Pandemic in Pekanbaru. To determine the effect of capital, training, and mentoring on the success of MSMEs in the Fashion Sector during the Covid-19 Pandemic in Pekanbaru. The population of this study is the fashion sector in Pekanbaru city. The sample selection technique was carried out using the probability sampling method of the mulitistage sampling model and obtained as many as 80 MSMEs. This research includes quantitative descriptive research and hypothesis testing is carried out with the help of SPSS statistical test tools. Capital has a significant effect on the business success of fashion sector MSMEs during the Covid-19 pandemic in Pekanbaru. This shows that the better the capital of MSME actors, the more the success of MSME businesses will increase. Training has a significant effect on the success of fashion sector MSME businesses during the Covid-19 pandemic in Pekanbaru. The more frequent the training provided, the more visible the development of MSMEs will be. Assistance has a significant effect on the success of MSME businesses in the fashion sector during the Covid-19 pandemic in Pekanbaru. This shows that the better the assistance to MSME actors, the more the success of MSME businesses will increase. There is a simultaneous influence of capital, training and mentoring on the success of MSME businesses. This shows that the better the business capital, the training received and the assistance obtained will affect the success of MSME businesses together.